2020
DOI: 10.1177/1178646920978241
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Plasma Kynurenine Metabolites Following One Bout of Sprint Interval Exercise

Abstract: The kynurenine pathway of tryptophan degradation produces several neuroactive metabolites suggested to be involved in a wide variety of diseases and disorders, however, technical challenges in reliably detecting these metabolites hampers cross-comparisons. The main objective of this study was to develop an accurate, robust and precise bioanalytical method for simultaneous quantification of ten plasma kynurenine metabolites. As a secondary aim, we applied this method on blood samples taken from healthy subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Although we did not measure peripheral or central serotonin levels, it is tempting to speculate that the TRP supplementation could have affected serotonin levels, and thus increasing wheel running activity. On the other hand, the number of studies addressing the effects of exercise on TRP catabolism through the KP are constantly increasing [ 14 , 15 , 25 , 26 , 27 , 28 , 29 ]. Once again, it is important to consider how the studies were planned when comparing data from the different sources.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not measure peripheral or central serotonin levels, it is tempting to speculate that the TRP supplementation could have affected serotonin levels, and thus increasing wheel running activity. On the other hand, the number of studies addressing the effects of exercise on TRP catabolism through the KP are constantly increasing [ 14 , 15 , 25 , 26 , 27 , 28 , 29 ]. Once again, it is important to consider how the studies were planned when comparing data from the different sources.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies have demonstrated that central fatigue may influence the reduction in the GMV in the cortical and subcortical regions (de Lange et al, 2005 ; Riccitelli et al, 2011 ; Arm et al, 2019 ). Higher concentrations of tryptophan and kynurenine have been observed in younger and older adults during prolonged physical exercise (Melancon et al, 2012 ; Strasser et al, 2016 ; Trepci et al, 2020 ). Prolonged physical activity and its high load in older athletes may be associated with structural deterioration due to central fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…186005662CV). Vials were transferred to an autosampler (set to 5 °C) that injected 1.5 μL into the ultra-performance liquid chromatography tandem mass spectrometry (UPLC–MS/MS) system [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…The flow rate used was 0.3 mL/min and the run time for each sample was 13.0 min. For more detailed and method validation see [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation